Usage of and satisfaction with Integrated Community Case Management care in western Uganda: a cross-sectional survey - Miller, James S.; Patel, Palka; McCarthy, Sara Mian; Wesuta, Andrew Christopher; Matte, Michael; Ntaro, Moses; Bwambale, Shem; Kenney, Jessica; Stone, Geren S.; Mulogo, Edgar Mugema (Malaria journal, 2021)
Background: In some areas of Uganda, village health workers (VHW) deliver Integrated Community Case Management (iCCM) care, providing initial assessment of children under 5 years of age as well as protocol-based treatment of malaria, pneumonia, and diarrhoea for eligible patients. Little is known about community perspectives on or satisfaction with iCCM care. This study examines usage of and satisfaction with iCCM care as well as potential associations between these outcomes and time required to travel to the household’s preferred health facility. Methods: A cross-sectional household survey was administered in a rural subcounty in western Uganda during December 2016, using a stratified random sampling approach in villages where iCCM care was available. Households were eligible if the household contained one or more children under 5 years of age. Results: A total of 271 households across 8 villages were included in the final sample. Of these, 39% reported that it took over an hour to reach their preferred health facility, and 73% reported walking to the health facility; 92% stated they had seen a VHW for iCCM care in the past, and 55% had seen a VHW in the month prior to the survey. Of respondents whose households had sought iCCM care, 60% rated their overall experience as “very good” or “excellent,” 97% stated they would seek iCCM care in the future, and 92% stated they were “confdent” or “very confdent” in the VHW’s overall abilities. Longer travel time to the household’s preferred health facility did not appear to be associated with higher propensity to seek iCCM care or higher overall satisfaction with iCCM care. Conclusions: In this setting, community usage of and satisfaction with iCCM care for malaria, pneumonia, and diar rhoea appears high overall. Ease of access to facility-based care did not appear to impact the choice to access iCCM care or satisfaction with iCCM care.
Keywords: Village health workers; Community health workers; Integrated Community Case Management; Patient satisfaction; Community perspective